(5t+3)-2*(t+3)=29-5t

Simple and best practice solution for (5t+3)-2*(t+3)=29-5t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5t+3)-2*(t+3)=29-5t equation:


Simplifying
(5t + 3) + -2(t + 3) = 29 + -5t

Reorder the terms:
(3 + 5t) + -2(t + 3) = 29 + -5t

Remove parenthesis around (3 + 5t)
3 + 5t + -2(t + 3) = 29 + -5t

Reorder the terms:
3 + 5t + -2(3 + t) = 29 + -5t
3 + 5t + (3 * -2 + t * -2) = 29 + -5t
3 + 5t + (-6 + -2t) = 29 + -5t

Reorder the terms:
3 + -6 + 5t + -2t = 29 + -5t

Combine like terms: 3 + -6 = -3
-3 + 5t + -2t = 29 + -5t

Combine like terms: 5t + -2t = 3t
-3 + 3t = 29 + -5t

Solving
-3 + 3t = 29 + -5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '5t' to each side of the equation.
-3 + 3t + 5t = 29 + -5t + 5t

Combine like terms: 3t + 5t = 8t
-3 + 8t = 29 + -5t + 5t

Combine like terms: -5t + 5t = 0
-3 + 8t = 29 + 0
-3 + 8t = 29

Add '3' to each side of the equation.
-3 + 3 + 8t = 29 + 3

Combine like terms: -3 + 3 = 0
0 + 8t = 29 + 3
8t = 29 + 3

Combine like terms: 29 + 3 = 32
8t = 32

Divide each side by '8'.
t = 4

Simplifying
t = 4

See similar equations:

| 14y^2-19y+4=11y^2+11y-5 | | 6f-2=6f-2 | | 3/4=n | | -7-26=n | | 8p+6-7p= | | y^2-9y+15=0 | | 4-x=5x+28 | | 2(2x+22)=8x-20 | | 5q+4q= | | 6y-10=0 | | 14+8x=32+8x | | 2x=60-5x | | m-6/5+3.8=7-2m | | -j+5j+2=14 | | 2(6-x)=3(1-x) | | 8y-2=6y+3 | | 5/4x-3/4y=9/4 | | 0.5*0.01= | | 5x^2+7=252 | | -2/3x+35=4/5x-31 | | 6n+9=-2n-23 | | 168-56= | | 1/5(15x+10) | | 2x+9=-7x-9 | | 3=2M/3+9 | | 3.5/6.3 | | 3(a+1)=11 | | 3x-199+x+75=180 | | 5x=3+2x-60 | | -.2x^2+5=0 | | -[-(-k)]-(-2)(-2+k)=-k-(4k+3) | | 14x7/2 |

Equations solver categories